PENGARUH ELECTRONIC WORD OF MOUTH (E-WOM) DAN DESTINATION IMAGE TERHADAP KEPUTUSAN BERKUNJUNG PADA WISATA HILLPARK SIBOLANGIT : (Studi Pada Pengunjung Hillpark Sibolangit) - Putri, Erlina; Adlina, Hafiza (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2024)
Tourism is a reference to a marker of a country's prosperity because the tourism industry has a real influence on the economy, economic improvement and environmental carrying capacity. This study aims to determine how the influence of E-WOM and destination image on visiting decisions on Hillpark Sibolangit tours. The research technique used is quantitative. The sampling technique was carried out by purposive sampling method with a sample size of 100 respondents. The results of this test indicate that the E-WOM factor (X1) and destination image (X2) have a partial and significant effect on visiting decisions (Y). E-WOM (X1) and destination image (X2) variables simultaneously and significantly affect visiting decisions (Y). With an R value of 0.724, it shows that the E-WOM (X1) and destination image (X2) factors are related to visiting decisions (Y) by 0.724 so that the relationship between these factors can be categorized as close. Through the R Square value, it is known that E-WOM (X1) and destination image (X2) contribute 51.4%, while the remaining 48.6% is influenced by variables not discussed in this study.